Art history at the crossroads of Ireland and the United States
1 online resource
Keywords: "Taking the visual arts as its focus, this anthology explores aspects of cultural exchange between Ireland and the United States. Art historians from both sides of the Atlantic examine the work of artists, art critics and art promoters. Through a close study of selected paintings and sculptures, photography and exhibitions from the nineteenth century to the present, the depth of the relationship between the two countries, as well as its complexity, is revealed. The book is intended for all who are interested in Irish/American interconnectedness and will be of particular interest to scholars and students of art history, visual culture, history, Irish studies and American studies"--